A Phenomenological Study on the Lived Experiences of Self-Aware-Non-Fluent English Teachers - Ushas Richel R. Rino; Glen P. Cortezano; Alberto D. Yazon; Karen A. Manaig; John Frederick B. Tesoro (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
This study delved into the lived experiences of self-aware-non-fluent English teachers in their instructional delivery to come up with practical strategies and ways to strengthen the delivery of instruction in using the English language. Accordingly, qualitative research design and hermeneutic phenomenological processes were utilized. In analyzing the acquired responses from the participants, the following steps were applied: (1) hermeneutic phenomenological reduction; (2) imaginative variation, where the possible meanings of horizons were attained through the individual and composite structural descriptions; lastly, (3) essence, where the synthesis and reflections were made to form implications. The epoche was also applied before and during the conduct of this qualitative research to suspend the researcher’s connection to the experiences of the participants and maintain bias-free data. Based on the testimonies gathered from the participants, 139 subordinate themes, 28 superordinate themes, and four (4) main themes were unveiled. Challenges encountered in using the English language in an English classroom, Practices in developing English language fluency in the classroom, Various training on enriching the English language fluency among English teachers; and Favorable experiences as English teachers were the four (4) main themes which highlighted all the significant occurrences in the classroom regarding English language fluency. As a result, a booklet entitled “I am a Pedagogue: Repertoire of English Fluency Enrichment Strategies” was crafted which emphasized strategies acquired from the lived experience of the participants and was intended to be applied by all the English teachers in Calamba City. Keywords – English teachers, enrichment strategies, instructional delivery, non-fluency